Foundation : the history of England from its earliest beginnings to the Tudors - Ackroyd, Peter, 1949- (Thomas Dunne Books, 2012)
One of Britain's most popular and esteemed historians tells the epic story of the birth of England. The first in an extraordinary six-volume history, "Foundation" takes the reader from the primeval forests of England's prehistory to the death, in 1509, of the first Tudor king, Henry VII.